Final answer:
The sum of the functions
and g(x) = 3x - 5 is
, which is obtained by adding the corresponding elements of each function and combining like terms.
Step-by-step explanation:
The question asks for the sum of two functions, F(x) and g(x). In mathematical terms, (f+g)(x) means we have to add the functions F(x) and g(x) together. This is done by adding the corresponding elements of each function.
Here are the given functions:
F(x) = 2x + 5x
g(x) = 3x - 5
To find (f+g)(x), we combine them like this:
(f+g)(x) = F(x) + g(x) = (2x + 5x) + (3x - 5)
Now, we simply combine like terms:
(f+g)(x) = 2x + 5x + 3x - 5
(f+g)(x) = 2x + 8x - 5
This is the simplified form of the sum of the functions F(x) and g(x).